Prosthetic rehabilitation of an osteoporosis case with semi precision attachments and cast partial dentures - A case report (Indian Journal of Case Reports, 2019)
Osteoporosis is a skeletal disorder that has emerged as a major health problem affecting mostly in the postmenopausal women and older individuals. In osteoporosis, there is an imbalance between the bone formation and bone resorption where in, there is an increase in resorption. It even affects the jaw bones making a challenging task for the prosthetic rehabilitation. Here, we present a case report of prosthetic rehabilitation of an osteoporosis case of 65-year-old woman, using semi precision attachments with Cast partial dentures.